Systematic literature reviews over the years - Beata Smela; Mondher Toumi; Karolina Świerk; Konrad Gawlik; Emilie Clay; Laurent Boyer (Taylor & Francis Group, 2023)
ABSTRACTPurpose: Nowadays, systematic literature reviews (SLRs) and meta-analyses are often placed at the top of the study hierarchy of evidence. The main objective of this paper is to evaluate the trends in SLRs of randomized controlled trials (RCTs) throughout the years.Methods: Medline database was searched, using a highly focused search strategy. Each paper was coded according to a specific ICD-10 code; the number of RCTs included in each evaluated SLR was also retrieved. All SLRs analyzing RCTs were included. Protocols, commentaries, or errata were excluded. No restrictions were applied.Results: A total of 7,465 titles and abstracts were analyzed, from which 6,892 were included for further analyses. There was a gradual increase in the number of annual published SLRs, with a significant increase in published articles during the last several years. Overall, the most frequently analyzed areas were diseases of the circulatory system (n = 750) and endocrine, nutritional, and metabolic diseases (n = 734). The majority of SLRs included between 11 and 50 RCTs each.Conclusions: The recognition of SLRs' usefulness is growing at an increasing speed, which is reflected by the growing number of published studies. The most frequently evaluated diseases are in alignment with leading causes of death and disability worldwide.